Evolution, Economic Competence, and the Market for Corporate Control - Pavel Pelikan (The Research Institute of Industrial Economics (IUI), 1989)
To assess the merits of the market for corporate control, this paper examines two processes which standard analysis does not study: the allocation of economic competence and the evolution of organizational structures. Economic competence is seen to be an unusual scarce resource embodied in the very ways in which individuals and organizations take economic decisions, which guides the allocation of all scarce resources, including itself. Its efficient allocation is shown to require an evolutionary trial-and-error process, where the market for corporate control plays a crucial role.
Keywords: D83; L22; 330; Corporate control; evolution of organisational structures; economic competence